A simulation model for gate operations in multi-purpose cargo terminals. Issue 8 (16th November 2016) - Keceli, Yavuz
ABSTRACT: A multi-purpose cargo terminal in a seaport contains necessary infrastructure to handle different types of cargo, such as container, dry bulk, general bulk, and Ro-Ro. Since such terminals generally have dedicated areas and equipment for different types of cargo, berth, and yard operations for each type of cargo can be considered separate. On the other hand, trucks that carry all types of cargo use the same gate structure to enter and leave the terminal. Therefore, a method to superimpose the traffic that is caused by different types of cargo is needed for the planning of gate investments and operations. Consequently, this paper has developed a simulation model for a multi-purpose terminal to estimate the gate traffic and determine the necessary gate infrastructure, so that it can be used as a decision support tool for terminal planners and operational managers.